The phenomenological-hermeneutic method of Gadamer. Some contributions to the approach of the circle of understanding - Rosales-Veítia, José (2024)
Gadamer's phenomenological-hermeneutic method has been used in various disciplines for the analysis and interpretation of texts. This article explores Gadamer's phenomenological-hermeneutic method and its application in the approach of the circle of understanding. Contributions such as the fusion of horizons and the importance of tradition in interpretation are presented. The objective is to identify some contributions that contribute to enriching the approach of the circle of understanding by offering conceptual and methodological tools to analyze and intervene in the processes of reading and interpreting texts.